Doping effect on the evolution of the pairing symmetry in n-type superconductor near antiferromagnetic phase boundary - Charikova, T.B.; Shelushinina, N.G.; Harus, G.I.; Neverov, V.N.; Petukhov, D.S.; Petukhova, O.E.; Ivanov, A.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2014)
We present the investigation results of the in-plane ρ(T) resistivity tensor at the temperature range 0.4–40 K in magnetic fields up to 90 kOe (H || c, J || ab) for electron-doped Nd2–xCexCuO4+δ with different degree of disorder near antiferromagnetic–superconducting phase boundary. We have experimentally found that for optimally doped compound both the upper critical field slope and the critical temperature decrease with increasing of the disorder parameter (d-wave pairing) while in the case of the underdoped system the critical temperature remains constant and dHc2/dT increases with increasing of the disorder (s-wave pairing). These features suggest a possible implementation of the complex mixture state as the s+id pairing.